Multiple Roles of Ret Signalling During Enteric Neurogenesis - Natarajan, Dipa; McCann, Conor; Dattani, Justine; Pachnis, Vassilis; Thapar, Nikhil (Frontiers in Molecular Neuroscience, 2022)
The majority of the enteric nervous system is formed by vagal neural crest cells which enter the foregut and migrate rostrocaudally to colonise the entire length of the gastrointestinal tract. Absence of enteric ganglia from the distal colon are the hallmark of Hirschsprung disease, a congenital disorder characterised by severe intestinal dysmotility. Mutations in the receptor tyrosine kinase RET have been identified in approximately 50% of familial cases of Hirschsprung disease but the cellular processes misregulated in this condition remain unclear. By lineage tracing neural crest cells in mice homozygous for a loss-of-function allele of Ret (Ret51/51), we demonstrate that normal activity of this receptor is required in vivo for the migration of enteric nervous system progenitors throughout the gut. In mutant mice, progenitors of enteric neurons fail to colonise the distal colon, indicating that failure of colonisation of the distal intestine is a major contributing factor for the pathogenesis of Hirschsprung disease. Enteric nervous system progenitors in the ganglionic proximal guts of mutant mice are also characterised by reduced proliferation and differentiation. These findings suggest that the functional abnormalities in Hirschsprung disease result from a combination of colonic aganglionosis and deficits in neuronal circuitry of more proximal gut segments. The reduced neurogenesis in the gut of Ret51/51 mutants was reproduced in the multilineage enteric nervous system progenitors isolated from these animals. Correction of the molecular defects of such progenitors fully restored their neurogenic potential in culture. These observations enhance our understanding of the pathogenesis of Hirschsprung disease and highlight potential approaches for its treatment.